Comparative Foraging Efficiency of Two Sympatric Jackals, Silver-Backed Jackals (Canis mesomelas) and Golden Jackals (Canis aureus), in the Ngorongoro Crater, Tanzania. (13th November 2016) - Temu, S. E.; Nahonyo, C. L.; Moehlman, P. D.
Abstract : The foraging efficiency of two sympatric species of jackals, silver-backed jackals ( Canis mesomelas ) and golden jackals ( Canis aureus ), was studied in the Ngorongoro crater from July 2014 through May 2015. The focal animal observation method was used and individuals of both species were followed as they foraged from morning to evening. Observations of individuals of both jackal species were made from a vehicle using binoculars and a spotting scope. Three major parameters were used for determination of foraging efficiency: distance travelled while foraging, time spent foraging, and amount of food secured in foraging period. The Mann–WhitneyU test showed no significant difference (P > 0.05 ) in distance travelled per unit time of foraging between the two species in the dry and wet seasons, respectively. Golden jackals secured a significantly higher amount of food than the silver-backed jackals in the wet season (Mann–WhitneyU test, P < 0.05, U = 1035.4 ). Hunting of prey larger than Thomson's gazelle ( Eudorcas thomsonii ) fawns was not common. Both species mainly fed on smaller prey such as invertebrates and rodents and scavenged opportunistically. Efficient foraging is crucial for both jackal species especially during their breeding season when they are provisioning dependent pups.